Beauty Influencer Credibility and Cosmetic Purchase Intention Among Undergraduate Beauty Education Students - Trisnani Widowati; Clarita Apriliani; Septian Eko Prasetyo; Anik Maghfiroh (Jurnal Penelitian Pendidikan, 2026)
The widespread use of social media has significantly influenced consumer behavior, particularly in the beauty industry, where beauty influencers serve as key sources of cosmetic information and recommendations. However, limited studies have explored how beauty influencer credibility affects cosmetic purchase intention among undergraduate beauty education students. This study aimed to examine the effect of beauty influencer credibility on cosmetic purchase intention among students of the Department of Beauty Education, Faculty of Engineering, Universitas Negeri Semarang. A quantitative explanatory design was employed involving 102 respondents selected through purposive sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using descriptive statistics and simple linear regression in IBM SPSS Statistics. The results showed that respondents reported high perceptions of beauty influencer credibility (M = 4.18, SD = 0.49) and cosmetic purchase intention (M = 4.06, SD = 0.56). Regression analysis revealed that beauty influencer credibility significantly influenced cosmetic purchase intention (β = 0.684, t = 9.487, p < 0.001), explaining 47.5% of the variance (R² = 0.475). These findings highlight the importance of influencer credibility in shaping consumers' purchase intentions and extend the application of Source Credibility Theory within beauty education. The study also offers practical implications for higher education institutions and the cosmetics industry in promoting digital consumer literacy and effective influencer marketing.